Comparison of monotherapy effect of phenytoin, carbamazapine and valproic acid in pediatric general tonic clonic and partial epilepsy - Muchamad Budi Nugroho; E. S. Herini; Sunartini Sunartini (Paediatrica Indonesiana, 2008)
Background Problems on epilepsy do not only depend on thedisease itself but also on management and drug regimens. Drugselection is very important to yield optimal treatment effect andto prevent side effects due to long-term therapy.Objective To determine whether there are any different effectsof monotherapy of phenytoin, carbamazapine, and valproic acidon pediatric general tonic clonic and partial epilepsy.Methods We conducted a historical cohort study on one monthuntil 18-years old children diagnosed as general tonic clonic orparsial epilepsy treated with phenytoin, carbamazapine, or valproicacid routinely for more than two years in Sardjito Hospital fromJanuary 2000 until May 2007. The sample size of each group was41. The main outcome was the time of 12-month remission,whereas the secondary outcomes were withdrawal from treatment,time to remission, side effects and cure rates.Results Valproic acid increased the possibility to achieve 12-monthremission (RR 2.66; 95%CI 1.06;6.65) compared to phenytoin,whereas carbamazapine did not (RR 1.47; 95%CI 0.66;3.28).Survival analysis showed that valproic acid was better thancarbamazapine (P=0.042) and phenytoin (P=0.007). There wereno significant differences among groups in the result of withdrawalfrom treatment, time to remission, and cure variables. The sideeffects of valproic acid seemed less than those of others.Conclusions Valproic acid increases the possibility of 12-monthremission compared to carbamazapine and phenytoin asmonotherapy in pediatric general tonic clonic and partial epilepsywithout increasing side effects. Carbamazapine has similar effectsof therapy to phenytoin.